Multiple Quorum Quenching Enzymes Are Active in the Nosocomial Pathogen Acinetobacter baumannii ATCC17978 - Mayer, Celia; Muras, Andrea; Romero, Manuel; López, María; Tomás, María; Otero, Ana (Frontiers in Cellular and Infection Microbiology, 2018)
Acinetobacter baumannii presents a typical luxI/luxR quorum sensing (QS) system (abaI/abaR) but the acyl-homoserine lactone (AHL) signal profile and factors controlling the production of QS signals in this species have not been determined yet. A very complex AHL profile was identified for A. baumannii ATCC17978 as well as for A. nosocomialis M2, but only when cultivated under static conditions, suggesting that surface or cell-to-cell contact is involved in the activation of the QS genes. The analysis of A. baumanni clinical isolates revealed a strain-specific AHL profile that was also affected by nutrient availability. The concentration of OHC12-HSL, the major AHL found in A. baumannii ATCC17978, peaked upon stationary-phase establishment and decreases steeply afterwards. Quorum quenching (QQ) activity was found in the cell extracts of A. baumannii ATCC17978, correlating with the disappearance of the AHLs from the culture media, indicating that AHL concentration may be self-regulated in this pathogen. Since QQ activity was observed in strains in which AidA, a novel α/β-hydrolase recently identified in A. baumannii, is not present, we have searched for additional QQ enzymes in A. baumannii ATCC17978. Seven putative AHL-lactonase sequences could be identified in the genome and the QQ activity of 3 of them could be confirmed. At least six of these lactonase sequences are also present in all clinical isolates as well as in A. nosocomialis M2. Surface-associated motility and biofilm formation could be blocked by the exogenous addition of the wide spectrum QQ enzyme Aii20J. The differential regulation of the QQ enzymes in A. baumannii ATCC17978 and the full dependence of important virulence factors on the QS system provides a strong evidence of the importance of the AHL-mediated QS/QQ network in this species.